Safety evaluation of the food enzyme carboxypeptidase D from the genetically modified Aspergillus oryzae strain NZYM‐MK - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme carboxypeptidase D (EC 3.4.16.6) is produced with the genetically modified Aspergillus oryzae strain NZYM‐MK by Novozymes A/S. It is free from viable cells of the production organism and its DNA. The genetic modifications do not give rise to safety concerns. The food enzyme is intended to be used in five food manufacturing processes. Dietary exposure to the food enzyme‐total organic solids (TOS) was estimated to be up to 0.908 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 2220 mg TOS/kg bw per day, the highest dose tested, which, when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 2445. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and two matches were found, one with a food allergen (wheat). The Panel considered that a risk of allergic reactions upon dietary exposure to this food enzyme, particularly in individuals sensitised to wheat, cannot be excluded, but will not exceed that of wheat consumption. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.